PERAN JOB DEMANDS DAN JOB RESOURCES TERHADAP WORK-FAMILY ENRICHMENT PADA GURU DI SEKOLAH X - Florensia Louhenapessy; Rita Markus Idulfilastri; P. Tommy Y.S. Suyasa (Jurnal Muara Ilmu Sosial, Humaniora, dan Seni, 2020)
The teacher plays two main roles in his life, namely the role in work and in the family. The implementation of these two roles does not always cause conflict, but can improve the quality of life of teachers. Teacher job conflicts are closely related to job demand and job resources. Therefore, the purpose of this study is to see how the role of job demands and job resources on work-family enrichment in teachers. Work-family enrichment is enrichment obtained from individual experiences at work towards the welfare of family life, or vice versa. Job demands are defined as identical job demands with various pressures on the job (job stressor). Examples of job demands on teachers are the number of students who exceed the capacity in the classroom, the addition of subject matter outside of the teacher's interest / competence, the demand to adjust science to the times. Job resources are physical, social, and organizational aspects that serve as support or resources to achieve work goals. With the existence of job resources, job demands can be resolved. Psychologically, solving work demands based on available resources will stimulate the individual to grow and develop personally, in this case the personal growth of the individual has implications for increasing his welfare in working / family life. Participants in this study were 43 teachers in School X. Analysis of research results using multiple regression showed that job demands and job resources together played a role in predicting an increase in work-family enrichment by 12.5%. The implication of the results of this study is that various demands on work supported by resources at work can improve welfare in working life / family life. Guru menjalankan dua peran utama dalam kehidupannya yaitu peran di pekerjaan dan keluarga. Menjalankan dua peran tersebut tidak selalu menimbulkan konflik, namun justru bisa meningkatkan kualitas hidup guru. Konflik pekerjaan guru sangat berhubungan dengan job demand dan job resources. Oleh karena itu, tujuan penelitian adalah untuk melihat bagaimana peran job demands dan job resources terhadap work-family enrichment pada guru. Work-family enrichment merupakan pengayaan yang diperoleh dari pengalaman-pengalaman individu di pekerjaan terhadap kesejahteraan kehidupan berkeluarga, atau sebaliknya. Job demands didefinisikan sebagai tuntutan-tuntutan pekerjaan yang indentik dengan berbagai tekanan dalam pekerjaan (job stressor). Contoh dari job demands pada guru adalah jumlah siswa yang melebihi kapasitas di dalam kelas, penambahan materi pelajaran di luar minat/kompetensi guru, tuntutan untuk menyesuaikan ilmu pengetahuan dengan perkembangan zaman. Job resources adalah aspek-aspek fisik, sosial, maupun organisasi yang berfungsi sebagai pendukung atau sumber daya untuk mencapai tujuan pekerjaan. Dengan adanya job resources maka job demands dapat terselesaikan. Secara psikologis, penyelesaian job demands berdasarkan job resources yang dimiliki akan menstimulasi individu untuk bertumbuh dan berkembang secara personal, dalam hal ini pertumbuhan personal yang dimiliki individu berimplikasi pada work-family enrichment. Partisipan pada penelitian ini adalah guru yang berjumlah 43 orang di Sekolah X. Analisis hasil penelitian yang menggunakan multiple regression menunjukan bahwa job demands dan job resources bersama-sama berperan memprediksi peningkatan work-family enrichment sebesar 12,5%.  Implikasi dari hasil penelitian ini bahwa berbagai tuntutan dalam pekerjaan yang di dukung dengan sumber daya dalam pekerjaan dapat meningkatkan kesejahteraan dalam kehidupan berkerja dan berkeluarga.